The Influence of Advances in Information Technology on the Development of Accounting Among Accounting Students Medan State University - Nurisky, Inez Bita; Gabriela, Michel; Aritonang, Luna Putri (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
Advances in information technology have had a significant impact on the development of accounting, especially in terms of accounting information systems. This research aims to analyze the influence of advances in information technology on the development of accounting, with a focus on accounting information systems. The research method used is a literature study using the keywords information technology, accounting developments, and accounting information systems. The research results show that advances in information technology have enabled the development of more efficient and effective accounting information systems. An accounting information system that is integrated with information technology can increase the accuracy and speed of data processing, and enable better decision-making. However, the use of information technology can also pose challenges, such as data security risks and the need for special skills in its use. Therefore, companies should carefully consider the use of information technology in their accounting information systems and ensure that they have sufficient resources to manage it.